APLIKASI PENGENALAN HEWAN LINDUNG MENGGUNAKAN AUGMENTED REALITY DENGAN METODE MARKER BASED TRACKING - Mufida, Mir'atul Khusna; Harun, Muhammad (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2018)
The existence of animals in Indonesia is now increasingly threatened along with the destruction of forest ecosystems and animal hunting. Many animals are now nearly extinct. Meanwhile, the introduction of Indonesian protected animals is only through the text media, images or video contained in the study book and internet. With limited knowledge about extinct animal many people still do not know about the animals and cause the lack of public awareness to help conserve protected animals in Indonesia. Augmented reality technology can be one of the media technologies that can be used for the introduction of animals to the community by benefitting from marker based tracking as the pattern of target identification. This article discusses an application development on how to bring animals’ 3D objects into smartphone in order to inform those which exist in Indonesia. From the results of questionnaires 30 respondents stated, the Application of Animal Protected Introduction has been very good in terms of display and 3D objects and has been good in terms of new information obtained.